Digital Transformation in School Administration Personnel Management: Applying Technology for Efficiency and Accountability - Aprilia, Nur Afni; Sultoni, Sultoni; Timan, Agus (Proceedings Series of Educational Studies, 2024)
This study discusses digital transformation in the management of school administrative personnel, which is a solution to improve efficiency and accountability in education management. The problem raised is the challenge faced by school administration personnel in managing administration conventionally. Such management often results in information delays and administrative errors. The purpose of this study is to explore the application of digital technology in school administration management and its impact on the performance of administrative staff. The method used includes the analysis of the review literature, namely by collecting, analyzing, and synthesizing various sources of literature relevant to the research topic. The results show that the application of information and communication technology significantly improves operational efficiency, accelerates decision-making, and increases accountability through a transparent reporting system. The conclusion of this study confirms that digital transformation not only reduces administrative workload, but also creates a more responsive and organized learning environment, supporting the achievement of higher educational goals.